Modern views on biological NO effects and its role in cardiovascular pathology pathogenesis - S. S. Parshina (Кардиоваскулярная терапия и профилактика)
The review contains updated information on biological NO effects and its role in cardiovascular pathology pathogenesis. Data on NO synthesis, metabolism, inactivation, positive and negative effects, and polyfunctional action are given. Mechanisms of NO regulatory system influence on main pathogenetic mechanisms in cardiovascular pathology: platelet hemostasis, hemocoagulation, blood rheology, functional status of vascular wall endothelial and smooth muscle components, stress-limiting factors, and lipid peroxidation – are described. The research on medication development, based on NO-generating substances, is presented, as well as data on a new prospective area: terahertz therapy at NO emission and absorption molecular specter frequencies (150,176…150, 644 HGz).